2017
DOI: 10.1111/zph.12389
|View full text |Cite
|
Sign up to set email alerts
|

Pet‐associated Campylobacteriosis: A persisting public health concern

Abstract: Campylobacter is regarded as a leading cause of human bacterial gastroenteritis in the United States. We report on a case of laboratory-confirmed Campylobacter jejuni infection in the Commonwealth of Pennsylvania among members of a household living with a laboratory-confirmed but non-speciated Campylobacter-infected puppy. We describe an outbreak of likely dog-associated campylobacteriosis, the risk factors, potential routes of exposure and the clinical features in the exposed family members, which began short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…Evidence for this includes risk factor analyses (Damborg et al 2016), the tendency for asymptomatic and intermittent or extended shedding of human-pathogenic Campylobacter bacteria by young dogs (Hald et al 2004, Parsons et al 2011) and several case studies where zoonotic transmission has been inferred (Damborg et al 2016). In one such case, raw feeding of puppies with chicken byproducts was documented (Campagnolo et al 2018).…”
Section: Campylobacter Speciesmentioning
confidence: 99%
“…Evidence for this includes risk factor analyses (Damborg et al 2016), the tendency for asymptomatic and intermittent or extended shedding of human-pathogenic Campylobacter bacteria by young dogs (Hald et al 2004, Parsons et al 2011) and several case studies where zoonotic transmission has been inferred (Damborg et al 2016). In one such case, raw feeding of puppies with chicken byproducts was documented (Campagnolo et al 2018).…”
Section: Campylobacter Speciesmentioning
confidence: 99%
“…Campylobacter jejuni is the species most commonly associated with human disease and is also the most frequent aetiology of canine campylobacteriosis (Campagnolo, Philipp, Long, & Hanshaw, ; Sokolow et al, ). Clinical signs occur more commonly in puppies vs. adult dogs, and these may include diarrhoea, lethargy, anorexia, and occasionally fever and vomiting (Acke, ; Marks, Rankin, Byrne, & Weese, ).…”
Section: Introductionmentioning
confidence: 99%
“…canine campylobacteriosis (Campagnolo, Philipp, Long, & Hanshaw, 2018;Sokolow et al, 2005). Clinical signs occur more commonly in puppies vs. adult dogs, and these may include diarrhoea, lethargy, anorexia, and occasionally fever and vomiting (Acke, 2018;Marks, Rankin, Byrne, & Weese, 2011).…”
mentioning
confidence: 99%
“…Local factors (including ingredient mix), effects of freeze-thawing, and detection methods may all have influenced these diverse findings. A small proportion of human campylobacteriosis cases are likely to be acquired through contact with pets, based upon risk factor analyses, case studies and the observed tendency for shedding of pathogenic Campylobacter species by young dogs (Campagnolo et al 2018;Damborg et al 2016;Hald et al 2004;Parsons et al 2011).…”
Section: Other Bacterial Speciesmentioning
confidence: 99%